2013
DOI: 10.1371/journal.pone.0071106
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Risk to Aboriginal Peoples: First Nations and Metis Responses to H1N1 Risk Messages

Abstract: Developing appropriate risk messages during challenging situations like public health outbreaks is complicated. The focus of this paper is on how First Nations and Metis people in Manitoba, Canada, responded to the public health management of pandemic H1N1, using a focus group methodology (n = 23 focus groups). Focus group conversations explored participant reactions to messaging regarding the identification of H1N1 virus risk groups, the H1N1 vaccine and how priority groups to receive the vaccine were establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 25 publications
0
48
0
3
Order By: Relevance
“…Unfortunately, most public health interventions that promote vaccination assume that vaccine hesitancy is due to inadequate knowledge about vaccines (the "knowledge deficit" approach) (35,36). However, as discussed OVERVIEW previously, the situation is complicated and underlying values and priorities compete with public health recommendations (43,44). Changing risk perception (a subjective judgment that people make about the characteristics and severity of a risk) through communication means that messages need to be tailored and targeted to account for the realities of community specific knowledge systems (e.g., adapted to address a vaccine scare peculiar to a specific context or tailored to religious beliefs of a specific community) and the unique information needs and preferences of particular communities (45,46).…”
Section: What Can Be Done About It?mentioning
confidence: 99%
“…Unfortunately, most public health interventions that promote vaccination assume that vaccine hesitancy is due to inadequate knowledge about vaccines (the "knowledge deficit" approach) (35,36). However, as discussed OVERVIEW previously, the situation is complicated and underlying values and priorities compete with public health recommendations (43,44). Changing risk perception (a subjective judgment that people make about the characteristics and severity of a risk) through communication means that messages need to be tailored and targeted to account for the realities of community specific knowledge systems (e.g., adapted to address a vaccine scare peculiar to a specific context or tailored to religious beliefs of a specific community) and the unique information needs and preferences of particular communities (45,46).…”
Section: What Can Be Done About It?mentioning
confidence: 99%
“…This is because they are most at risk when planning for, communicating, and managing responses associated with pandemic outbreaks. 70 Similarly, evaluations of the risk communication practice during the H1N1 outbreak involving Pacific Peoples and Māori in New Zealand, 71 Australian Aboriginal, and Torres Strait Islander communities [72][73][74] concluded that more community-based information dissemination mechanisms were needed to avoid problems created by generic prevention and control messages.…”
Section: Segmentation In the Public Spherementioning
confidence: 99%
“…So, what explanations have been identified in the literature on why risk communication by organizations fails? Several studies point out that government agencies fail to address target groups by providing culturally relevant and meaningful information on risk; this is particularly valid in the case of local communities and minority groups (Chess, Burger, & McDermott, ; Driedger, Cooper, Jardine, Furgal, & Bartlett, ; Jardine, ; Jardine, Boyd, & Furgal, ). Another explanation put forward is that agencies lack shared perspectives (Chess, Salomone, & Hance, ; Chess, Salomone, Hance, & Saville, ).…”
Section: Introductionmentioning
confidence: 99%